A Pilot Study Using the Gynecologic Cancer Lymphedema Questionnaire (GCLQ) as a Clinical Care Tool to Identify Lower Extremity Lymphedema in Gynecologic Cancer Survivors - Carter, Jeanne (Gynecol Oncol, 2010)
OBJECTIVE: To determine the feasibility and efficacy of using the Gynecologic Cancer Lymphedema Questionnaire (GCLQ) as a symptom scale for lymphedema of the lower extremity (LLE). METHODS: Twenty-eight gynecologic cancer survivors with documented LLE and 30 without a history or presence of lymphedema completed the GCLQ and provided feedback about their satisfaction with and feasibility of using the GCLQ at their oncology follow-ups. The study survey took approximately 5–10 minutes to complete, and it was easily understood by the majority of the sample. RESULTS: Participants had a mean age of 59.6 years (range, 28–80 years). Twenty-eight women (48%) had LLE and 30 (52%) had no history or presence of LLE (confirmed by limb volume [LV] measurements at assessment). Type of cancer history included: endometrial, 38 (66%); cervical, 13 (22%); and vulvar, 7 (12%). GCLQ scores differed significantly by lymphedema diagnosis; LLE patients had higher scores (P<0.01). The large area under the curve (AUC) of 0.95 (95% CI: 0.90–1.000) suggests that the GCLQ can distinguish between patients with and without LLE. Although all 28 (100%) of the LLE patients were aware of their LLE diagnosis, only 23 (82%) underwent treatment. The GCLQ was easily understood by most (55/58, 95%); and overall, patients showed a high willingness (56/58, 96%) to complete the questionnaire at future appointments. Twenty-five (88%) of the LLE patients found the GCLQ to be helpful in identifying symptoms of lymphedema. CONCLUSIONS: The GCLQ effectively distinguished between gynecologic cancer survivors with and those without LLE, with good sensitivity and specificity. The patients, particularly those with LLE, showed high confidence in the GCLQ’s ability to detect LLE symptoms.